Efektivitas Strategi REACT (Relating, Experiencing, Applying, Cooperating, Transfering) Terhadap Hasil Belajar dan Keterampilan Proses Sains di SMP N 22 Bandar Lampung - Sri Latifah; Mery Kusyeni (Jurnal Penelitian Pembelajaran Fisika, 2017)
The aims of this research are to knoweffectiveness examine result and sains proces skill students using a strategy REACT (Relating,Eksperiencing,Applying,Cooperating, The research methode using is Quasi Experiment. Instrument research using test is essay  examinine for examine result learning and non test is observasion sheet for sains proces skill. According research result using independent sampel t testanlysis of the data postest shows that thitung > ttabel (4,900>2,001) and percentage average of observasion sheet control and experimen class shows that thitung >ttabel (2,979 >2,001). Then effectiveness of strategy REACT a given with effect size test obtain d=0,3 is included in the medium. The conclusion that H1is acceptance there is influence result learinng and sains proces skill students using strategy REACT and effectiveness against result learning.The aims of this research are to knoweffectiveness examine result and sains proces skill students using a strategy REACT (Relating,Eksperiencing,Applying,Cooperating, The research methode using is Quasi Experiment. Instrument research using test is essay  examinine for examine result learning and non test is observasion sheet for sains proces skill. According research result using independent sampel t testanlysis of the data postest shows that thitung > ttabel (4,900>2,001) and percentage average of observasion sheet control and experimen class shows that thitung >ttabel (2,979 >2,001). Then effectiveness of strategy REACT a given with effect size test obtain d=0,3 is included in the medium. The conclusion that H1is acceptance there is influence result learinng and sains proces skill students using strategy REACT and effectiveness against result learning.